2020
DOI: 10.3390/atmos11101109
|View full text |Cite
|
Sign up to set email alerts
|

SST Warming in Recent Decades in the Gulf Stream Extension Region and Its Impact on Atmospheric Rivers

Abstract: The sea surface temperature (SST) front in the Gulf Stream (GS) extension region is important to synoptic variations in atmosphere. In winter, large amounts of heat and moisture are released from the SST front, modulating the baroclinicity and humidity of the atmosphere, which is important for extratropical cyclones and atmospheric rivers (ARs). In this study, the variation of SST in the North Atlantic in winters since 1981 is investigated using satellite and reanalysis datasets, and a 23-year (1997 to 2019) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
3
1
0
Order By: Relevance
“…It can be observed that, along the upper stream of the GS extension, the SST gradient was smaller in NAT+ years (Figure 2b). The profile of the zonal-averaged (between 65° W and 55° W) SST gradient shows an increase in ocean front between 40° N and 42° N during NAT− years, which agrees with the finding in Wu et al [18]. The effect of this SST gradient variation on ARs is discussed in Section 4.…”
Section: Decadal Variation Of Ars In Relation To the Natsupporting
confidence: 90%
See 1 more Smart Citation
“…It can be observed that, along the upper stream of the GS extension, the SST gradient was smaller in NAT+ years (Figure 2b). The profile of the zonal-averaged (between 65° W and 55° W) SST gradient shows an increase in ocean front between 40° N and 42° N during NAT− years, which agrees with the finding in Wu et al [18]. The effect of this SST gradient variation on ARs is discussed in Section 4.…”
Section: Decadal Variation Of Ars In Relation To the Natsupporting
confidence: 90%
“…Second, from the EOF1 distribution of NAT mode (Figure 1b), we noted a positive SST signal spreading along the GS ocean front. This suggests a difference in the GS front between the two NAT modes, which may also induce the response of ARs in the North Atlantic, as suggested in the work conducted by Wu et al [18]. The ARs induce extreme rain during landfall in western Europe; for example, the 95% extreme rainfall in Norway and the UK shows much higher and lower occurrence tendency during NAT+ and NAT− modes (Figure 1d), respectively.…”
Section: Introductionsupporting
confidence: 57%
“…The most consistent statistically significant increasing trends are for ARs associated with mature cyclones in the Upper Midwest/Great Lakes regions, which position the most intense IVT over the southeast US and Tennessee River Valley, and are rooted in the Gulf of Mexico. Trends are also consistent with coastal cyclones over the northeast US with the most intense IVT transiting the Mid‐Atlantic and Northeast US Recent studies have found similar increasing trends for IVT and moisture transport in the study domain which can feedback on the AR metrics associated with some Nor'easter forced ARs (Teale & Robinson, 2022; Y. Wu et al., 2020).…”
Section: Discussionsupporting
confidence: 74%
“…The asymmetric atmospheric responses to warm and cold eddies result in net moisture transport above the planetary boundary layer (PBL) and the moisture entering above the PBL interacts with upper level higher momentum within the extratropical cyclones, favorable for AR genesis and subsequent downstream water vapor transport. Other studies have also shown that the GS front can increase moisture availability and affect the frequency and intensity of landfalling ARs over Western Europe (Wu et al 2020;Zavadoff and Kirtman 2020;McClenny et al 2020). These studies highlight the importance of oceanic front and eddies in modifying the moisture supply in ARs, primarily through potential thermodynamic responses to mesoscale SSTs.…”
Section: Introductionmentioning
confidence: 72%